1995
DOI: 10.1073/pnas.92.21.9510
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex binding affinity of an antigenic determinant is crucial for the differential secretion of interleukin 4/5 or interferon gamma by T cells.

Abstract: Differential activation of CD4+ T-cell precursors in vivo leads to the development of effectors with unique patterns of lymphokine secretion. To investigate whether the differential pattern of lymphokine secretion is influenced by factors associated with either the display and/or recognition of the ligand, we have used a set of ligands with various class II binding affinities but unchanged T-cell specificity. The ligand that exhibited -10,000-fold higher binding to I-AU considerably increased the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
114
3

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(124 citation statements)
references
References 36 publications
7
114
3
Order By: Relevance
“…It has been established for mice and man that while high affinity ligands for MHC class II molecules may induce T helper cells to secrete IFN-γ (Th1 response) [10], low affinity ligands may induce the secretion of IL-4 and IL-5 (Th2 response) [13,19]. In addition to playing different roles in host defense, inappropriate Th1/Th2 responses have also been associated with certain diseases [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been established for mice and man that while high affinity ligands for MHC class II molecules may induce T helper cells to secrete IFN-γ (Th1 response) [10], low affinity ligands may induce the secretion of IL-4 and IL-5 (Th2 response) [13,19]. In addition to playing different roles in host defense, inappropriate Th1/Th2 responses have also been associated with certain diseases [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that while high affinity ligands for MHC class II (e.g. HLA DRA*0101) [10] may induce T helper cells to secrete IFN-γ and IL-2 (Th1 response), low affinity ligands can induce IL-4 and IL-5 (Th2 response) [13,19]. It is speculated that high affinity interactions between peptides and MHC molecules can lead to increase in the number of stable MHC-peptide complexes on the surface of the antigen presenting cells, which augment the avidity of MHC-peptide-T-cell receptor (TCR) interactions [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively infrequent IL-10 response to peptide p91-110 compared with the frequent IFN-g response (Fig. 3) may also indicate that this peptide drives a predominantly Type 1 response, perhaps as a consequence of its high-affinity binding to a wide range of HLA-DR molecules [10,30].…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies support this view. It has been reported that antigenic peptides that bind well to MHC molecules and/or TCR favour the generation of IFN-g-producing cells, whereas peptides that bind less well do not [30,31]. Additionally, it has been shown that TCR transgenic CD4 þ T cells differentiate into IFN-g-producing T cells only when high antigen doses are used for priming [32].…”
Section: Discussionmentioning
confidence: 99%